Animal cloning applications in agriculture. - Page, R.L (IEEE Engineering in medicine and biology magazine)
The scope of this article will be to outline the potential benefits of cloning technology to the animal agricultural industry and highlight some of the possibilities for combining the tools offered by nuclear transfer, animal genomics, and genetic engineering to make improved animal agricultural products.